Resposta :
Resposta:
x, = 5
x,, = 4
Explicação passo-a-passo:
-3x² +27x -60 = 0
3x² -27x +60 = 0
a = 3
b = -27
c = 60
∆ = b² -4ac
∆ = (-27)² -4 .3 .60
∆ = 729 -720
∆ = 9
[tex]x = \frac{ - b( + \: ou \: - ) \sqrt{(delta)} }{2a} [/tex]
[tex]x = \frac{ - ( - 27)( + \: ou \: - ) \sqrt{9} }{2 \times 3} [/tex]
[tex]x = \frac{27( + \: ou \: - )3}{6} [/tex]
[tex]x {}^{.} = \frac{27 + 3}{6} [/tex]
[tex]x {}^{.} = \frac{30}{6} [/tex]
[tex]x {}^{.} = 5[/tex]
[tex]x {}^{..} = \frac{27 - 3}{6} [/tex]
[tex]x {}^{..} = \frac{24}{6} [/tex]
[tex]x {}^{..} = 4[/tex]